EFFECT OF LOGISTICS COSTS ON EXPORT AND COMPANY PERFORMANCE: A RESEARCH ON TRC 1 REGION COMPANIES - Uygur, Mehmet Nedım; Catuk, Cuneyt; Uzun, Erkan (My University, 2023)
The aim of this study is to measure the effect of logistics costs on firm performance and export performance. In this context, a research was conducted on 391 businesses registered to the Chamber of Industry and Commerce of the TRC 1 region (Gaziantep, Adıyaman and Kilis). In the research, logistics cost scale developed by Hai and Son (2019), firm performance scale developed by Ellinger et al. (2002) and export performance scale developed by Navarro et al. (2010) were used. SPSS 25 program was used for analyzing the data. A factor analysis was performed on each variable in order to determine how much of the total variance the variables explained and to determine how consistent the questions about each variable were. As a result of the factor analysis, logistics cost variable and export performance variables consist of one sub-dimension, firm performance variable consists of two sub-dimensions, logistics cost variable has 63,577% of total variance, Firm Performance variable is 64,726% of total variance, and Export performance variable is 75.458 percent of total variance. As a result of the factor analysis, it was also concluded that the questions regarding these variables were compatible with each other. Normality test was performed to measure whether the scales were normally distributed and it was seen that the data were normally distributed. Reliability analysis was performed to measure whether the scales were reliable and it was determined that the scale was highly reliable. Correlation analysis was performed to measure the relationship between the factors, and as a result of the correlation analysis, it was concluded that there was a moderately significant relationship of 0.361 between logistics costs and firm performance, and a low-level insignificant relationship of 0.045 between logistics costs and export performance. As a result of the regression analysis, it was seen that logistics costs explained 13% of the changes in firm performance and each unit increase in logistics cost appropriateness created an increase of 0.288 in firm performance. Considering the sigma value, it is concluded that logistics costs have a positive and significant effect on firm performance.
Keywords: Firm performance; export performance; Logistics cost